Lost relations : fortunes of my family in Australia's Golden Age - Davison, Graeme, 1940- (Allen & Unwin, 2015)
Through the lives of two generations of his forebears, one of Australia's most respected historians tells the story of English free settlers arriving in the mid-19th century: the miners, millers, storekeepers, free selectors and railwaymen who built the Australia we know today.